2021
DOI: 10.3390/ijerph18030920
|View full text |Cite
|
Sign up to set email alerts
|

Radon Activity Concentrations in Natural Hot Spring Water: Dose Assessment and Health Perspective

Abstract: The world community has long used natural hot springs for tourist and medicinal purposes. In Indonesia, the province of West Java, which is naturally surrounded by volcanoes, is the main destination for hot spring tourism. This paper is the first report on radon measurements in tourism natural hot spring water in Indonesia as part of radiation protection for public health. The purpose of this paper is to study the contribution of radon doses from natural hot spring water and thereby facilitate radiation protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Several drinking water samples have radon concentrations exceeding 100 Bq L −1 . The United States Environmental Protection Agency (USEPA) proposed a maximum contaminant level (MCL) for radon in drinking water of 11 Bq L −1 and an alternative maximum contaminant level (AMCL) of 148 Bq L −1 29 , 30 . On the other hand, the European Union (EU) recommended that the reference level for 222 Rn in drinking water is 100 Bq L −1 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Several drinking water samples have radon concentrations exceeding 100 Bq L −1 . The United States Environmental Protection Agency (USEPA) proposed a maximum contaminant level (MCL) for radon in drinking water of 11 Bq L −1 and an alternative maximum contaminant level (AMCL) of 148 Bq L −1 29 , 30 . On the other hand, the European Union (EU) recommended that the reference level for 222 Rn in drinking water is 100 Bq L −1 31 .…”
Section: Discussionmentioning
confidence: 99%
“…When SSNTD CR-39 detectors are to be used for radon monitoring, the following recommendations were concluded to be important: (1) to check the track density for new and old CR-39 detectors due to different material compositions; and (2) to check the effects of pre-etching treatments when comparing or interpreting experimental results in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The track sensitivity of detectors was obtained from geometrical parameters of each detector using the formula of Equation (1). The tendency of sensitivities can be attributed to the physical nature of track formation and overetched tracks.…”
Section: Radon Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A detailed study on the radiation exposure pathways in that area showed that, to such total effective dose, the radionuclide inhalation ( 222 Rn and 220 Rn isotopes) contributed with 70%, the ambient gamma radiation from radionuclides in the ground contributed with 29%, the cosmic radiation contributed with 0.5%, and the ingestion of local foods and water contributed with 0.5% [37]. Another study for an HBRA in Mamuju, Indonesia, reported a similar percent contribution of exposure pathways and radon isotopes to the average effective dose for inhabitants, determined at 32 mSv y −1 (range 17-155 mSv y −1 ) [88]. Detailed studies such as these ones are missing for most of the HBRAs referred above.…”
Section: Echassières Auvergne Region Francementioning
confidence: 98%